2017
DOI: 10.1016/j.archoralbio.2016.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Altered autophagy and sympathetic innervation in salivary glands from high-fat diet mice

Abstract: 2 Highlights: Adiponectin levels decreased in the High Fat Diet group after three months  Autophagy increased after three months of High Fat Diet  mTOR showed no activation regarding the time point studied  Tyrosine hydroxylase decreased after two and three month of High Fat Diet Abstract Objective: to investigate the effects of a high fat diet (HFD) on salivary glands in vivo, in a mouse model. In particular, whether it will induce the appearance of fat cells in salivary glands, alterations related to aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Previous studies showed that HFD-induced lipid accumulation in the kidney could have an onset as early as at 2 months, 32 whereas 3 months on this diet failed to induce lipid deposition in the salivary gland. 33 In this study, lipid deposition was already apparent in the lacrimal gland after 1 month on the HFD. The rapidity of this change indicates that the lacrimal gland is more sensitive to hyperlipidemia.…”
Section: Discussionmentioning
confidence: 46%
“…Previous studies showed that HFD-induced lipid accumulation in the kidney could have an onset as early as at 2 months, 32 whereas 3 months on this diet failed to induce lipid deposition in the salivary gland. 33 In this study, lipid deposition was already apparent in the lacrimal gland after 1 month on the HFD. The rapidity of this change indicates that the lacrimal gland is more sensitive to hyperlipidemia.…”
Section: Discussionmentioning
confidence: 46%
“…In-vivo, Adiponectin secretion is regulated by the degree of obesity (Carbone et al, 2012). Its secretion is inversely proportional to the amount of adipose tissue (Swarbrick and Havel, 2008;Benedix et al, 2011;de Carvalho et al, 2017). It has been shown that patients with type 2 diabetes and obesity have lower serum Adiponectin levels than normal weight individuals (Cao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the saliva secretions were also regulated by parasympathetic and sympathetic innervations (Proctor and Carpenter, 2014). Tyrosine hydroxylase, a useful marker of sympathetic nerves, significantly decreased after 2 and 3 months of HFD in submandibular glands (de Carvalho et al, 2017), which may explain the decrease in gland secretions. Additionally, HFD could perturb B-cell production, activity, and maturation by changing the composition of the gut microbiome (Shaikh et al, 2015;Petta et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…HFD alone could induce a series of pathologic changes in the lacrimal gland (He et al, 2020). However, HFD failed to induce lipid deposition in the salivary gland (de Carvalho et al, 2017). On the other hand, the saliva secretions were also regulated by parasympathetic and sympathetic innervations (Proctor and Carpenter, 2014).…”
Section: Discussionmentioning
confidence: 99%